Growth Performance and Ruminal Metabolic Variables of Goats Fed Rain Tree (Samanea saman) Pods - M. J. Morais; C. C. Sevilla; J. T. Dizon; G. L. Manulat; E. E. C. Abes; A. A. Angeles (Tropical Animal Science Journal, 2018)
The effect of rain tree pods (RTP) or acacia pods on the growth performance, rumen metabolites, and digestibility of dry matter (DM) and crude protein (CP) in goats was evaluated through feeding trial and in situ methods. Eighteen 7 month-old Philippine native goats with body weight range of 7.86±1.28 kg were divided into three groups consisting of six replicates and randomly assigned to one of treatment diets containing 0%, 50%, and 100% RTP in the concentrate portion of a ration containing 65% roughage and 35% concentrate. Three rumen-cannulated mature goats were used in the in situ studies to determine the dietary effects on rumen fluid pH, total volatile fatty acids (VFA), ammonia, and rumen DM and CP digestibilities.  Differences (P values < 0.05) were observed on daily gain, total feed intake, and feed efficiency with diets having >50% RTP generally resulted in lower above-stated performance parameters.  Rumen fluid pH of goats decreased after feeding and was lowest in goats fed with 50% RTP. Concentrations of VFA and ammonia were not significantly different. Slowly degradable DM of the test diets were higher in concentrate mixture without RTP. Degradable fractions of CP had highest value on concentrate mixture without RTP while lowest on 100% RTP. However, no differences were observed on potentially digestible fractions and degradability constants of DM and CP. It could be concluded that RTPs can be an alternative ingredient in concentrate mixtures given up to 50% in the mixture as part of a daily ration for goats.